Analysis of Room Allocation Based on Age in Nursing Homes Using the C4.5 Decision Tree Method - Zulham Sitorus; Muhammad Indra (Yayasan Sinergi Multidimensi Kreatif, 2024)
This study analyzes the effectiveness of the C4.5 Decision Tree algorithm in managing room allocation in nursing homes based on the residents' ages. Using a dataset of 333 entries, which includes age and room names, the study aims to determine the most suitable room placements. The analysis process involves preprocessing the data to simplify the dataset, followed by the application of the C4.5 Decision Tree model using the RapidMiner platform. The results indicate that the algorithm effectively classifies residents into room names such as Jambu, Nenas, Jeruk, and others based on their age. These findings provide insights into how age influences room placement in nursing homes and enable more optimal facility management. The study also recommends considering additional factors in further analyses to enhance the accuracy of resident placement.